Periodic limb movements during sleep and blood pressure changes in sleep apnoea: Data from the European Sleep Apnoea Database. Issue 8 (24th December 2019) - Lombardi, Carolina; Parati, Gianfranco; Soranna, Davide; Zambon, Antonella; Sliwinski, Paweł; Roisman, Gabriel; Pepin, Jean‐Louis; Schiza, Sophia; Riha, Renata; Joppa, Pavol; Fietze, Ingo; Hedner, Jan; et al.
ABSTRACT: Background and objective: OSA and PLMS are known to induce acute BP swings during sleep. Our current study aimed to address the independent effect of PLMS on BP in an unselected OSA patient cohort. Methods: This cross‐sectional analysis included 1487 patients (1110 males, no previous hypertension diagnosis or treatment, mean age: 52.5 years, mean BMI: 30.5 kg/m 2 ) with significant OSA (defined as AHI ≥ 10) recruited from the European Sleep Apnoea Cohort. Patients underwent overnight PSG. Patients were stratified into two groups: patients with significant PLMS (PLMSI > 25 events/hour of sleep) and patients without significant PLMS (PLMSI < 25 events/hour of sleep). SBP, DBP and PP were the variables of interest. For each of these, a multivariate regression linear model was fitted to evaluate the relationship between PLMS and outcome adjusting for sociodemographic and clinical covariates (gender, age, BMI, AHI, ESS, diabetes, smoking and sleep efficiency). Results: The univariate analysis of SBP showed an increment of BP equal to 4.70 mm Hg ( P  < 0.001) in patients with significant PLMS compared to patients without significant PLMS. This increment remained significant after implementing a multivariate regression model (2.64 mm Hg, P = 0.044). No significant increment of BP was observed for DBP and PP. Conclusion: PLMS is associated with a rise in SBP regardless of AHI, independent of clinical and sociodemographic confounders. A PLMS phenotype may carry an increased risk for cardiovascular disease in OSA patients. Abstract : The link between PLMS and cardiovascular alterations is still debated. Our current study aimed to address the effects of PLMS on BP in a large unselected OSA patient cohort, showing that the PLMS phenotype is associated with significantly elevated clinical SBP independent of confounders. See related Editorial